2022
DOI: 10.3389/fcomm.2022.984340
|View full text |Cite
|
Sign up to set email alerts
|

Arabic metalinguistic knowledge predicts reading comprehension: A scoping review

Abstract: Arabic is a language with unique characteristics, yet the role metalinguistic skills (i. e., phonological awareness, morphological awareness, and orthographical knowledge) play in the development of reading and reading comprehension in Arabic is not well understood. This review aims to: (1) synthesize studies that examine metalinguistic skills' contribution to reading comprehension in Arabic, (2) emphasize gaps and limitations within the current body of literature, and (3) offer recommendations for further res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…They concluded that teachers could not answer half of the questions correctly, and almost two-thirds lacked basic explicit knowledge. Similarly, in a recent study of 221 Saudi Arabian teachers, Bin Sawad & Law (2022) found that, on average, teachers struggled to correctly answer one-half of the explicit metalinguistic knowledge items presented, where the average teacher participant could only properly answer 11 of the 28 questions.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…They concluded that teachers could not answer half of the questions correctly, and almost two-thirds lacked basic explicit knowledge. Similarly, in a recent study of 221 Saudi Arabian teachers, Bin Sawad & Law (2022) found that, on average, teachers struggled to correctly answer one-half of the explicit metalinguistic knowledge items presented, where the average teacher participant could only properly answer 11 of the 28 questions.…”
Section: Introductionmentioning
confidence: 89%
“…Within the Rational Planning model, the learners' needs are first identified, and then learning outcomes are selected accordingly, followed by the designation of the teaching approach. Accordingly, the training offered within this study was developed after applying the Arabic metalinguistic knowledge assessment tool to identify teachers' difficulties (Bin Sawad & Law, 2022). To examine the relative difficulty of the metalinguistic knowledge assessment items, Rasch model analysis for a dichotomous response was used (Devrilmez et al, 2019).…”
Section: Training Designmentioning
confidence: 99%
See 3 more Smart Citations